On the origin of strengthening mechanisms in Ni-Mo alloys prepared via powder metallurgy. (5th January 2017) - Yang, Chao; Muránsky, Ondrej; Zhu, Hanliang; Thorogood, Gordon J.; Huang, Hefei; Zhou, Xingtai
Abstract: A new class of materials, which rely on the dispersion strengthening of SiC particles in addition to precipitation strengthening by nano-precipitates is being developed for the application in molten salt nuclear reactors. A battery of dispersion and precipitation strengthened (DPS) NiMo-based alloys containing varying amount of SiC (0.5–2.5 wt.%) was prepared via a mechanical alloying (MA) route followed by spark plasma sintering (SPS), rapid cooling, high-temperature annealing and water quenching. Lab X-ray Diffraction (XRD), Electron Back Scattering Diffraction (EBSD), and Transmission Electron Microscopy (TEM) were employed in the microstructural characterization of this new type of alloys. It is shown that the NiMo matrix of these alloys is effectively reinforced by dispersion of SiC from the initial powder mixture and nano-Ni3 Si precipitates, which precipitated during the sintering/annealing process. Furthermore, the matrix is strengthened by solid-solution of Mo in Ni. As a result, these newly developed NiMo alloys take advantage of dispersion, precipitation and solid solution strengthening, which leads to their superior mechanical properties. Graphical abstract: A Ni-SiC composite is a class of the carbide dispersion strengthening (CDS) materials developed for the use in the future generation of Molten Salt Reactors (MSRs). However, it has been shown that the strength of this material is not satisfactory due to the large spacing between present SiC particles. Hence, in this work we designed a new class of materials, which can keep the advantages of SiC dispersion strengthening in addition to formation of nano-precipitates to further strengthen the material. A number of dispersion – precipitation strengthened (DPS) NiMo-based alloys containing varying amount of SiC (0.5–2.5 wt.%) was prepared via a mechanical alloying (MA) route followed by spark plasma sintering (SPS), rapid cooling, high-temperature annealing and water quenching. Lab X-ray Diffraction (XRD), Electron Back Scattering Diffraction (EBSD), and Transmission Electron Microscopy (TEM) were employed in the microstructural characterization. The Ni-Mo matrix of these new alloys is reinforced by dispersion strengthening of residual (unreacted) SiC particles from the initial powder mixture in addition to precipitation strengthening of nano-Ni3 Si precipitates, which precipitated during the sintering/annealing process. Furthermore, the matrix is strengthened by solid-solution of Mo in Ni. As a result, these newly developed NiMo-based DPS alloys relies on the combination of dispersion, precipitation and solid-solution strengthening leading to superior mechanical properties. Highlights: A new design for a class of materials Combination of dispersion, precipitation and solid-solution strengthening Significant improvement of mechanical properties